Exploring Parental Factors Related to Weight Management in Survivors of Childhood Central Nervous System Tumors. (March 2014) - Santa Maria, Diane; Swartz, Maria C.; Markham, Christine; Chandra, Joya; McCurdy, Sheryl; Basen-Engquist, Karen
Childhood central nervous system tumor survivors (CCNSTS) are at risk for adverse health issues. Little research has been conducted to explore the role of parental factors in weight management to mitigate adverse health outcomes. We conducted 9 group interviews (n = 20) with CCNSTS, their parents, and health care providers to ascertain parental factors that may influence weight management practices in CCNSTS. Three main themes were identified: parenting style, parent–child connectedness, and food and physical activity (PA) environment. Although most parents adopted an authoritative parenting style related to diet and PA practices, some adopted a permissive parenting style. Participants expressed high levels of connection that may hinder the development of peer relationships and described the food and PA environments that promote or hinder weight management through parental modeling of healthy eating and PA and access to healthy food and activities. Weight management interventions for CCNSTS may experience greater benefit from using a family-focused approach, promoting positive food and PA environments, parental modeling of healthy eating and exercise, and partnering with youth to adopt weight management behaviors.